Biodegradable materials in dentistry: A comprehensive review of current trends - Kambala, Meena Lakshmi Reddy; Dalli, Swetha Reddy; Kandikatla, Pradeep; Marna, Anil Kumar (International Journal of Dental Materials, 2024)
The dental industry has witnessed a paradigm shift towards biodegradable materials, driven by the need for sustainable and environmentally friendly solutions. Biodegradable materials in dentistry offer a promising alternative to traditional non-degradable materials, providing many benefits for patients, clinicians, and the environment. However, challenges persist, including limited durability and standardized regulations. This review article explores the current state of biodegradable materials in dentistry, including their applications, advantages, and limitations. Further, this article discussed the use of biodegradable materials in dental implants, restoratives, and temporary devices, as well as their potential for tissue engineering and regenerative dentistry. Additionally, the discussion covered the clinical significance, emphasizing the possibility of biodegradable materials transforming dental procedures and reducing their environmental footprint. As the field continues to evolve, biodegradable materials are poised to play a vital role in shaping the future of sustainable dentistry.